The chairperson and CEO roles interaction and responses to strategic tensions. Issue 1 (5th February 2018) - Morais, Filipe; Kakabadse, Andrew; Kakabadse, Nada
Abstract : Purpose: The purpose of this paper is to use Stewart's model of role as a lense from which to explore chairperson and CEO role dynamics in addressing strategic paradox and tension. Design/methodology/approach: The paper draws on 29 semi-structured, in-depth interviews with chairpersons and CEOs of UK-listed companies. Interview data are subjected to role analysis using Stewart's (1982) Demands-Constraints-Choice (DCC) model of role. Findings: Findings indicate that relationship levels of trust, communication and chairperson time enable strategic tensions to be raised and confronted in the relationship reducing defensiveness. Two distinct approaches to handle strategic tensions are found. The CEO-led approach predominates and rests on less flexible role boundaries, requiring the chairperson to proactively identify strategic tensions and perform an advisory/mentoring role. The shared leadership approach, less prevalent, rests on highly flexible role boundaries where the skills and experience of each incumbent become more relevant, enabling the separation of efforts and integration of strategic tensions in the relationship in a "dynamic complementarity of function". Research limitations/implications: The paper only applies to the UK context and is limited to contexts where CEO and chairperson roles are separate. The paper draws on individual perceptions of chairperson and CEOs (i.e. not pairs). Practical implications: The paper provides insights to practicing CEOs and chairperson on two distinct ways of working through strategic paradox and tensions. Originality/value: The paper adds to the scarce literature at chairperson and CEO roles and strategic paradox and tension.